Assessment of the Level of Accountability in the Context of the Development of Autonomy of Public Universities in Vietnam - Cuong, Pham Le; Thu Hang, Nguyen Thi; Manh, Pham Dinh; Lam, Phan Quoc; Hung, Pham Minh (International Journal of Criminology and Sociology, 2022)
The purpose of the study was the development of a methodological approach to assessing the subordination of the level of honor and autonomy of universities in Vietnam. Methodology: a survey aimed at assessing the level of perception of respondents about the need to carry out accountable activities and assessing the real level of accountability of the studied universities in Vietnam. The survey included 559 managers and 448 teachers from 5 public universities in Vietnam. Correlation analysis of statistical data processing to empirically assess the density and nature of the relationship between the level of perception of need and the actual level of accountability of Vietnamese universities. Main Findings: the Vietnamese universities under study are characterized by an average level of actual accountability, which does not contribute to the effective development of their autonomy in modern conditions. Given that the level of perception of the need for accountability by university personnel and its actual level of implementation have a direct subordinate relationship, it seems necessary to introduce effective mechanisms of accountability based on the motivation of personnel of higher education institutions in Vietnam. Applications of this Study: the results of this research study will be useful to the government authorities of Vietnam, as well as the administration of educational institutions for the development and practical implementation of an effective strategy for increasing the autonomy of institutions of the higher education system in Vietnam, as a factor in the optimal ratio of state and market mechanisms in achieving socio-economic progress. Novelty/Originality of this Study: The authors empirically determined the level of perception and actual accountability of universities in Vietnam, as well as quantitatively substantiated the qualitative parameters of their interaction in the process of developing the autonomy of higher educational institutions.